Selected readings on information technology management contemporary issues - Kelley, George, 1960- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2009)
This book supplements course instruction and student research with quality articles focused on key issues concerning the management and utilization of information technology. Containing over 30 chapters from authors across the globe, these selected readings in areas such as information systems, knowledge management, and IT governance depict the most relevant and important areas of classroom discussion within the categories of Fundamental Concepts and Theories; Development and Design Methodologies; Tools and Technologies; Application and Utilization; Critical Issues; and Emerging Trends.